Case Report: Two Cases of Pediatric Thrombotic Thrombocytopenic Purpura Treated With Combined Therapy - Tripiciano, Costanza; Zangari, Paola; Montanari, Mauro; Leone, Giovanna; Massella, Laura; Garaboldi, Lucia; Massoud, Michela; Lancellotti, Stefano; Strocchio, Luisa; Manno, Emma Concetta; Palma, Paolo; Corsetti, Tiziana; et al. (Frontiers in Pediatrics, 2021)
Thrombotic thrombocytopenic purpura (TTP) is a thrombotic microangiopathy caused by a severely reduced activity of the von Willebrand factor-cleaving protease ADAMTS13. Over 95% of TTP are acquired, due to autoantibodies inhibitors. In children, acquired TTP is a very rare, life-threatening disease. To date, no consensus exists on the treatment strategy of pediatric TTP. We report the cases of two pediatric patients with a diagnosis of TTP, successfully treated with the combination of various therapeutic approaches. Although the patients complained different set of symptoms, laboratory data showed a Coombs negative hemolytic anemia, renal impairment, and low platelet count in both cases. The diagnosis of acquired TTP was supported by the Plasmic score and confirmed by the reduction of the ADAMTS13 activity and the presence of anti-ADAMTS13 antibodies. Intravenous immunoglobulin, corticosteroids, and Plasma Exchange (PEX) were performed without delay. As soon as available, Caplacizumab was added to the therapy, with a prompt normalization of platelet count. Nevertheless, ADAMTS13 activity was persistently low and anti-ADAMTS13 antibodies level was high; thus, a course of Rituximab was administered, with persistent normalization of laboratory findings. No adverse events were observed during the treatment. In our experience, the combined use of PEX, Caplacizumab and immunosuppressive therapy during the acute phase of the disease is safe and may have a significant impact on the prognosis with successful clinical outcome and the decrease of life-threatening events.